Strategic Spatial Planning of Territorial Communities to achieve the Sustainable Development Goals - Сергій Бортник; Тетяна Лаврук; Віліна Пересадько (Вісник Харківського національного університету імені В.Н. Каразіна. Серія Геологія. Географія. Екологія)
Problem Statement. Strategic spatial planning in Ukraine focuses mainly on economic aspects and takes less into account the environmental consequences of planned activities, which may be threatening to natural and cultural heritage. This is explained, in particular, by the insufficient number of trained specialists for planning sustainable spatial development. It is especially important to integrate scientific natural research into educational programs for training specialists in spatial planning, which include the study of geodiversity, the evolution of natural and cultural landscapes, methods of creating nature conservation areas, the formation of eco-networks, as well as the introduction of innovative technologies in land use and various branches of the national economy. Such research is the basis for developing community strategy and achieving the Sustainable Development Goals (SDGs), effective territorial management and successful spatial planning practices.